Solving and Modeling Ken-ken Puzzle byUsingHybridGeneticsAlgorithm - Olivia Johanna; Samuel Lukas; Kie Van Ivanky Saputra (Bandar Lampung University (UBL), 2012)
Kenken is logic puzzle which similar to Sudoku. The basic rules are same as Sudoku. As in sudoku, the goal of each puzzle is to fill a grid with digits 1 through 4 for a 4Ã4 grid, 1 through 5 for a 5Ã5, etc. No digit appears more than once in any row or column. Grids range in size from 3Ã3 to 9Ã9. Unlike sudoku, KenKen grids are divided into heavily outlined groups of cells often called âcagesâ and the numbers in the cells of each cage must produce a certain âtargetâ number when combined using a specified mathematical operation (addition, subtraction, multiplication or division). ). For example, a three-cell cage specifying addition and a target number of 6 in a 4Ã4 puzzle might be satisfied with the digits 1, 2, and 3. Digits may be repeated within a cage, as long as they are not in the same row or column. No operation is relevant for a single-cell cage: placing the